Parasites and their (endo)symbiotic microbes - Yurchenko, Vyacheslav; Lukeš, Julius (Parasitology, 2018)
Thanks to modern molecular biology methods, our understanding of the impact of (endo)symbiotic bacteria on parasitic protists and helminths is growing fast. In this issue, 9 papers have been brought together that describe various facets of the relationships between these microorganisms, reveal their range and high frequency, as well as their capacity to create novel biological complexity. Comparative analyses of these host-endosymbiont interactions indicate that there may be no discrete types of relationships but rather a continuum ranging from a dispensable endosymbiont minimally integrated within the host cell to organelles, such as mitochondria and plastids that evolved into an indispensable, deeply integrated components of the cell. We hope that this series of studies on parasites and (endo)symbiotic bacteria will increase awareness about these relationships and their representation in microbial ecology models.
Keywords: Parasites; Animals; symbióza; paraziti; organely; zvířata; biologická evoluce; Biological Evolution; Organelles; Symbiosis